Combinatorial functional and differential equations applied to differential posets - Menni, Matías (2008)
We give combinatorial proofs of the primary results developed by Stanley for deriving enumerative properties of differential posets. In order to do this we extend the theory of combinatorial differential equations developed by Leroux and Viennot. © 2007 Elsevier B.V. -- Keywords: Differential posets;Y-graphs; Joyal species; Combinatorial differential equations
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 06/03/2009)
Discrete Mathematics, Volume 308, Issue 10, 28 May 2008, pages 1864-1888.
Keywords: MATEMÁTICAS DISCRETAS; COMBINATORIA; ECUACIONES DIFERENCIALES